Perancangan Sistem Penjualan Produk Kerajinan dan Makanan Pada Bisnis Lokal di Batusangkar Menggunakan Platform Digital Berbasis Opencart - Syahrani, Selfira; Annas, Firdaus; Nabilah, Rizky (JOVISHE : Journal of Visionary Sharia Economy, 2024)
This research emphasizes the importance of modern technology for data management and improving business effectiveness, particularly in designing a product sales system. The aim of this article is to design a sales system for handicraft and food products based in Batusangkar using digital platforms such as OpenCart. The current issue faced by local businesses in Batusangkar is that marketing has not yet been widely implemented because many MSMEs have not utilized online promotional media. Furthermore, the rapidly developing technology is seen as capable of improving sales effectiveness while expanding market reach. The development model used in this research is the Research and Development (R&D) model with the ADDIE approach, which includes Analysis, Design, Development, Implementation, and Evaluation. The final result of this research is a promotional media using a digital platform, specifically OpenCart, designed to make it easier for local entrepreneurs to manage and market their products. The findings from this study show that using a digital platform like OpenCart not only helps improve business effectiveness but also enhances the competitiveness and marketability of local businesses in Batusangkar. With the sales system utilizing a digital platform, local entrepreneurs in Batusangkar can expand and improve the marketability of their products.